Shenqi Yizhi granules protect hippocampus of AD transgenic mice by modulating on multiple pathological processes. (5th December 2020) - Ren, Jianting; Wei, Dongfeng; An, Haiting; Zhang, Junying; Zhang, Zhanjun
Abstract: Ethnopharmacological relevance: Chinese herbal medicine (CHM) draws more attention to explore effective therapeutic strategy for Alzheimer's disease (AD). CHM usually uses combinations of herbs or herbal ingredients to treat diseases, with the components targeting different disease processes. CHM might improve cognition in AD and MCI patients by optimizing network activity, promoting neural plasticity and repairing damaged neurons. Shenqi Yizhi granules (SQYG), a CHM prescription, are mainly consists of Panax ginseng C.A.Mey, Astragalus membranaceus (Fisch.) Bunge, and Scutellaria baicalensis Georgi and have been used to ameliorate cognitive impairment in mild-to-moderate dementia patients. Aim of the study: To investigate the neuroprotection effect and pharmacological mechanism of SQYG in the hippocampus of 5XFAD transgenic mice. Materials and methods: The immunofluorescence detection, 2DE-gels, mass spectrum identification, biological information analysis and Western blot were performed after SQYG treatment. Results: SQYG treatment significantly decreased the fluorescence intensities of anti-GFAP and anti-Iba1 in the hippocampus of 5XFAD mice. The expression levels of 31 proteins in the hippocampus were significantly influenced by SQYG, approximately 65% of these proteins are related to energy metabolism, stress response and cytoskeleton, whereas others are related to synaptic transmission, signal transduction, antioxidation, amino acid metabolism, and DNA repair. The expression of these proteins were increased. The changes in the expression levels of malate dehydrogenase (cytoplasmic) and pyruvate kinase M were confirmed by Western blot. Conclusions: The pharmacological mechanism of SQYG on the hippocampus may be related to modulation of multiple pathological processes, including energy metabolism, stress response, cytoskeleton, synaptic transmission, signal transduction, and amino acid metabolism in 5XFAD mice. Graphical abstract: Image 1 Highlights: Shenqi Yizhi granules (SQYG) is a traditional Chinese herbal prescription. SQYG can ameliorate cognitive impairment in mild-to-moderate dementia. The proteome-wide protein alterations induced by SQYG were investigated in the hippocampus of 5XFAD mice. This study provides insights into the pharmacological mechanism of SQYG in the hippocampus of 5XFAD mice.